Solutionbank: Edexcel AS and A Level Modular Mathematics
Solutionbank: Edexcel AS and A Level Modular Mathematics
Solutionbank: Edexcel AS and A Level Modular Mathematics
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise A, Question 1
Question:
(b)
file://C:\Users\Buba\kaz\ouba\c3_2_a_1.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 2 of 2
(c)
(d)
file://C:\Users\Buba\kaz\ouba\c3_2_a_1.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 2
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise A, Question 2
Question:
file://C:\Users\Buba\kaz\ouba\c3_2_a_2.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 2 of 2
Solution:
x 2x is doubling
3a so a = 6
1
b9 so b 2 = 9 b=4 2
x3
x 4 is subtract 3, then divide by 4
10 e so e = ( 10 3 ) 4 = 1.75
f3
f5 so 4 =5 f = 23
1
So a = 6, b = 4 2 , c = 0, d = 3, e = 1.75, f = 23, g = 2 6, h = 6
file://C:\Users\Buba\kaz\ouba\c3_2_a_2.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 1
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise B, Question 1
Question:
Find:
(d) j ( 2 ) where j : x 2 x
Solution:
(a) f
( x ) = 5x + 1
Substitute x = 3 f ( 3 ) = 5 3 + 1 = 16
( x ) = 3x2 2
(b) g
Substitute x = 2 g ( 2 ) = 3 ( 2 ) 2 2 = 3 4 2 = 10
( x ) = 3x
(c) h
Substitute x = 0 h ( 0 ) = 30 = 1
(x) =2x
(d) j
Substitute x = 2 j ( 2 ) = 2 ( 2 ) = 22 = 4
Pearson Education Ltd 2008
file://C:\Users\Buba\kaz\ouba\c3_2_b_1.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 1
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise B, Question 2
Question:
(a) p ( a ) = 16 where p ( x ) = 3x 2
(b) q ( b ) = 17 where q ( x ) = x2 3
(c) r ( c ) = 34 where r ( x ) = 2 ( 2x ) + 2
(d) s ( d ) = 0 where s ( x ) = x2 + x 6
Solution:
(a) p ( x ) = 3x 2
Substitute x = a and p ( a ) = 16 then
16 = 3a 2
18 = 3a
a=6
( x ) = x2 3
(b) q
Substitute x = b and q ( b ) = 17 then
17 = b2 3
20 = b2
b = \ 20
b= 25
( x ) = 2 2x + 2
(c) r
Substitute x = c and r ( c ) = 34 then
34 = 2 2c + 2
32 = 2 2c
16 = 2c
c=4
( x ) = x2 + x 6
(d) s
Substitute x = d and s ( d ) = 0 then
0 = d2 + d 6
0= (d+3) (d2)
d = 2, 3
Pearson Education Ltd 2008
file://C:\Users\Buba\kaz\ouba\c3_2_b_2.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 3
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise B, Question 3
Question:
(a) m ( x ) = 3x + 2
(b) n ( x ) = x2 + 5
(c) p ( x ) = sin ( x )
(d) q ( x ) = x3
Solution:
(a) m ( x ) = 3x + 2
(i)
(b) n ( x ) = x2 + 5
(i)
file://C:\Users\Buba\kaz\ouba\c3_2_b_3.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 2 of 3
(ii)Range of n ( x ) is n ( x ) 5
(iii) Function is many-to-one
(c) p ( x ) = sin ( x )
(i)
(ii)Range of p ( x ) is 1 p(x) 1
(iii) Function is many-to-one
(d) q ( x ) = x3
(i)
file://C:\Users\Buba\kaz\ouba\c3_2_b_3.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 3 of 3
file://C:\Users\Buba\kaz\ouba\c3_2_b_3.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 4
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise B, Question 4
Question:
State whether or not the following graphs represent functions. Give reasons for
your answers and describe the type of function.
(a)
(b)
(c)
file://C:\Users\Buba\kaz\ouba\c3_2_b_4.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 2 of 4
(d)
(e)
(f)
Solution:
(a)
One-to-one function
file://C:\Users\Buba\kaz\ouba\c3_2_b_4.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 3 of 4
(b)
One-to-one function
(c)
Not a function.
The values left of x = a do not get mapped anywhere.
The values right of x = a get mapped to two values of y.
(d)
file://C:\Users\Buba\kaz\ouba\c3_2_b_4.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 4 of 4
(e)
file://C:\Users\Buba\kaz\ouba\c3_2_b_4.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 3
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise C, Question 1
Question:
Solution:
file://C:\Users\Buba\kaz\ouba\c3_2_c_1.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 2 of 3
(i)
(i)
file://C:\Users\Buba\kaz\ouba\c3_2_c_1.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 3 of 3
file://C:\Users\Buba\kaz\ouba\c3_2_c_1.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 3
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise C, Question 2
Question:
(b) n ( x ) = x2 + 5 for x 2
file://C:\Users\Buba\kaz\ouba\c3_2_c_2.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 2 of 3
(i)
2 sin x has the same shape as sin x except that it has been stretched by a factor of
2 parallel to the y axis.
(ii) Range of p(x) is 0 p ( x ) 2
(iii) The function is many-to-one
(d) q ( x ) = + \ x + 2 for x 2
(i)
file://C:\Users\Buba\kaz\ouba\c3_2_c_2.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 3 of 3
file://C:\Users\Buba\kaz\ouba\c3_2_c_2.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 2
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise C, Question 3
Question:
(a) f(3)
(b) f(10)
g(x) is not a function because the element 4 of the domain does not get mapped
anywhere.
In f(x) it gets mapped to 25.
file://C:\Users\Buba\kaz\ouba\c3_2_c_3.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 2 of 2
file://C:\Users\Buba\kaz\ouba\c3_2_c_3.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 2
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise C, Question 4
Question:
(c) Find the values of the domain that get mapped to themselves in the range.
Solution:
(a) x
2
6 is a -shaped quadratic with a minimum value of ( 0 , 6 ) .
10 x is a linear function with gradient 1 passing through 10 on the y axis.
file://C:\Users\Buba\kaz\ouba\c3_2_c_4.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 2 of 2
s ( a ) = 43
a2 6 = 43
a2 = 49
a= 7
Value is negative so a = 7
file://C:\Users\Buba\kaz\ouba\c3_2_c_4.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 1
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise C, Question 5
Question:
g ( x ) = cx + d
g ( 3 ) = 10 c 3 + d = 10
g ( 8 ) = 12 c 8 + d = 12
3c + d = 10
8c + d = 12
: 5c = 2 ( 5)
c = 0.4
Substitute c = 0.4 into :
3 0.4 + d = 10
1.2 + d = 10
d = 8.8
Hence g ( x ) = 0.4x + 8.8
Pearson Education Ltd 2008
file://C:\Users\Buba\kaz\ouba\c3_2_c_5.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 1
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise C, Question 6
Question:
f ( x ) = ax3 + bx 5
f ( 1 ) = 4 a 13 + b 1 5 = 4
a+b5= 4
a+b=1
f(2) =9 a 23 + b 2 5 = 9
8a + 2b 5 = 9
8a + 2b = 14
4a + b = 7
: 3a = 6
a=2
Substitute a = 2 in :
2+b=1
b= 1
Pearson Education Ltd 2008
file://C:\Users\Buba\kaz\ouba\c3_2_c_6.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 2
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise C, Question 7
Question:
h ( x ) = x2 6x + 20 = ( x 3 ) 2 9 + 20 = ( x 3 ) 2 + 11
This is a -shaped quadratic with minimum point at (3, 11).
file://C:\Users\Buba\kaz\ouba\c3_2_c_7.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 2 of 2
file://C:\Users\Buba\kaz\ouba\c3_2_c_7.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 1
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise D, Question 1
Question:
1
Given the functions f ( x ) = 4x + 1, g ( x ) = x2 4 and h ( x ) = x
, find
expressions for the functions:
(a) fg (x)
(b) gf (x)
(c) gh (x)
(d) fh (x)
(e) f
2 (x)
Solution:
(a) fg ( x ) = f ( x2 4 ) = 4 ( x2 4 ) + 1 = 4x2 15
(b) gf ( x ) = g ( 4x + 1 ) = ( 4x + 1 ) 2 4 = 16x2 + 8x 3
1 1 2 1
(c) gh (x) =g = 4= 2 4
x x x
1 1 4
(d) fh (x) =f =4 + 1 = x +1
x x
(e) f
2 ( x ) = ff ( x ) = f ( 4x + 1 ) = 4 ( 4x + 1 ) + 1 = 16x + 5
Pearson Education Ltd 2008
file://C:\Users\Buba\kaz\ouba\c3_2_d_1.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 3
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise D, Question 2
Question:
For the following functions f(x) and g(x), find the composite functions fg(x) and
gf(x). In each case find a suitable domain and the corresponding range when
(a) f ( x ) = x 1, g ( x ) = x2
(b) f ( x ) = x 3, g ( x ) = + x
(c) f ( x ) = 2x, g ( x ) = x + 3
Solution:
(a) f( x ) = x 1, g ( x ) = x2
fg ( x ) = f ( x2 ) = x2 1
Domain x
Range fg ( x ) 1
gf ( x ) = g ( x 1 ) = ( x 1 ) 2
Domain x
Range gf ( x ) 0
file://C:\Users\Buba\kaz\ouba\c3_2_d_2.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 2 of 3
(b) f( x ) = x 3, g ( x ) = + x
fg ( x ) = f ( + x ) = x 3
Domain x 0
(It will not be defined for negative numbers)
Range fg ( x ) 3
gf ( x ) = g ( x 3 ) = \ x 3
Domain x 3
Range gf ( x ) 0
(c) f( x ) = 2x, g ( x ) = x + 3
fg ( x ) = f ( x + 3 ) = 2x + 3
Domain x
Range fg ( x ) > 0
file://C:\Users\Buba\kaz\ouba\c3_2_d_2.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 3 of 3
gf ( x ) = g ( 2x ) = 2x + 3
Domain x
Range gf ( x ) > 3
file://C:\Users\Buba\kaz\ouba\c3_2_d_2.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 1
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise D, Question 3
Question:
f ( x ) = 3x 2, g ( x ) = x2
fg ( x ) = f ( x2 ) = 3x2 2
gf ( x ) = g ( 3x 2 ) = ( 3x 2 ) 2
If fg ( a ) = gf ( a )
3a2 2 = ( 3a 2 ) 2
3a2 2 = 9a2 12a + 4
0 = 6a2 12a + 6
0 = a2 2a + 1
0= (a1) 2
Hence a = 1
Pearson Education Ltd 2008
file://C:\Users\Buba\kaz\ouba\c3_2_d_3.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 1
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise D, Question 4
Question:
1
Given that s ( x ) = x2
and t ( x ) = 3x + 4 find the number m such that ts
( m ) = 16.
Solution:
1
s(x) = x 2, t ( x ) = 3x + 4
1 1 3
ts ( x ) = t =3 + 4 = x2 + 4
x2 x2
If ts ( m ) = 16
3
m2 + 4 = 16 ( 4)
3
m2 = 12 [ (m2) ]
3 = 12 ( m 2 ) ( 12 )
3
12 =m2
0.25 = m 2
m = 2.25
Pearson Education Ltd 2008
file://C:\Users\Buba\kaz\ouba\c3_2_d_4.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 2
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise D, Question 5
Question:
(a) 4x +3
(b) 4x
2 + 4x
1
(c)
x2 + 4
2
(d)
x+5
+1
(e) ( x2 1 ) 3
(f) 2x
2 1
(g) x
27
Solution:
(a) 4x + 3 = 2 ( 2x + 1 ) + 1 = 2 l ( x ) + 1 = ll ( x ) [or l2 ( x ) ]
(b) 4x
2 + 4x = ( 2x + 1 ) 2 1 = [ l ( x ) ] 2 1 = ml ( x )
1 1 1
(c) = = m(x) +5 = nm ( x )
x2 + 4 ( x2 1 ) + 5
2 1
(d) x + 5 +1=2 x+5 + 1 = 2 n ( x ) + 1 = ln ( x )
(e) ( x2 1 ) 3 = [ m ( x ) ] 3 = pm ( x )
(f) 2x
2 1 = 2 ( x2 1 ) + 1 = 2 m ( x ) + 1 = lm ( x )
file://C:\Users\Buba\kaz\ouba\c3_2_d_5.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 2 of 2
(g) x
27
= [ ( x3 ) 3 ] 3 = { [ p ( x ) ] 3 { 3 = [ pp ( x ) ] 3 = ppp ( x )
= p3 ( x )
Pearson Education Ltd 2008
file://C:\Users\Buba\kaz\ouba\c3_2_d_5.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 1
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise D, Question 6
Question:
x3
If m ( x ) = 2x + 3 and n ( x ) = 2
, prove that mn ( x ) = x.
Solution:
x3
m ( x ) = 2x + 3, n ( x ) = 2
file://C:\Users\Buba\kaz\ouba\c3_2_d_6.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 1
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise D, Question 7
Question:
3 3x
If s ( x ) = x+1
and t(x) = x
, prove that st ( x ) = x.
Solution:
3 3x
s(x) = x + 1, t(x) = x
file://C:\Users\Buba\kaz\ouba\c3_2_d_7.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 1
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise D, Question 8
Question:
1 x+1
If f ( x ) = x+1
, prove that f2 ( x ) = x+2
. Hence find an expression for f3 ( x ) .
Solution:
1
f(x) = x+1
file://C:\Users\Buba\kaz\ouba\c3_2_d_8.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 4
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise E, Question 1
Question:
For the following functions f(x), sketch the graphs of f(x) and f 1 ( x ) on the
same set of axes. Determine also the equation of f 1 ( x ) .
(a) f ( x ) = 2x + 3 { x {
x
(b) f (x) = 2
x
1
(c) f (x) = x
x, x0
(e) f ( x ) = x2 + 2 { x , x 0{
(f) f ( x ) = x3 { x {
Solution:
(a)If y = 2x + 3
y 3 = 2x
y3
2 =x
x3
Hence f 1 ( x ) = 2
file://C:\Users\Buba\kaz\ouba\c3_2_e_1.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 2 of 4
x
(b) If y = 2
2y = x
Hence f 1 ( x ) = 2x
1
(c) If y = x
yx = 1
1
x= y
1
Hence f 1 ( x ) = x
Note that the inverse to the function is identical to the function.
file://C:\Users\Buba\kaz\ouba\c3_2_e_1.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 3 of 4
If y = 4 x
(d)
x+y=4
x=4y
Hence f 1 ( x ) = 4 x
Note that the inverse to the function is identical to the function.
(e)If y = x2 + 2
y 2 = x2
\y2=x
Hence f 1 ( x ) = \ x 2
file://C:\Users\Buba\kaz\ouba\c3_2_e_1.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 4 of 4
(f)If y = x3
3\ y = x
Hence f 1 ( x ) = 3\ x
file://C:\Users\Buba\kaz\ouba\c3_2_e_1.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 1
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise E, Question 2
Question:
Determine which of the functions in Question 1 are self inverses. (That is to say
the function and its inverse are identical.)
Solution:
file://C:\Users\Buba\kaz\ouba\c3_2_e_2.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 1
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise E, Question 3
Question:
g(x) =4x
has domain x > 0
and range g ( x ) < 4
Hence g 1 ( x ) = 4 x
has domain x < 4
and range g 1 ( x ) > 0
Although g(x) and g 1 ( x ) have identical equations they act on different
numbers and so are not identical. See graph.
Pearson Education Ltd 2008
file://C:\Users\Buba\kaz\ouba\c3_2_e_3.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 5
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise E, Question 4
Question:
For the following functions g(x), sketch the graphs of g(x) and g 1 ( x ) on the
same set of axes. Determine the equation of g 1 ( x ) , taking care with its
domain.
1
(a) g (x) = x
x, x 3
(b) g ( x ) = 2x 1 { x , x 0{
3
(c) g (x) = x2
x, x>2
(e) g ( x ) = x2 + 2 { x , x > 4 {
(f) g ( x ) = x3 8 { x , x 2{
Solution:
(a)
file://C:\Users\Buba\kaz\ouba\c3_2_e_4.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 2 of 5
1
g(x) = x x, x 3
1
has range g ( x ) , 0 < g ( x ) 3
Changing the subject of the formula gives
1 1
g 1 (x) = x, 0<x
x 3
(b)
g ( x ) = 2x 1 { x , x 0{
has range g ( x ) , g ( x ) 1
Changing the subject of the formula gives
x+1
g 1 (x) = x, x 1
2
file://C:\Users\Buba\kaz\ouba\c3_2_e_4.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 3 of 5
(c)
3
g(x) = x2 x, x>2
has range g ( x ) , g ( x ) > 0
Changing the subject of the formula gives
3
y= x2
y(x2) =3
3
x2= y
3 3 + 2y
x= +2 or
y y
3 3 + 2x
Hence g 1 ( x ) = +2 or
x x
{x, x>0{
file://C:\Users\Buba\kaz\ouba\c3_2_e_4.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 4 of 5
(d)
g ( x ) = x2 + 2 { x , x > 4 {
has range g ( x ) , g ( x ) > 18
Changing the subject of the formula gives
g 1 ( x ) = \ x 2 with domain x , x > 18
file://C:\Users\Buba\kaz\ouba\c3_2_e_4.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 5 of 5
(f)
g ( x ) = x3 8 { x , x 2{
has range g ( x ) , g ( x ) 0
Changing the subject of the formula gives
y = x3 8
y + 8 = x3
3\ y + 8 = x
file://C:\Users\Buba\kaz\ouba\c3_2_e_4.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 2
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise E, Question 5
Question:
m ( x ) = x2 + 4x + 9 { x , x > a { .
Let y = x2 + 4x + 9
y= (x+2) 24+9
y= (x+2) 2+5
This has a minimum value of ( 2 , 5 ) .
file://C:\Users\Buba\kaz\ouba\c3_2_e_5.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 2 of 2
file://C:\Users\Buba\kaz\ouba\c3_2_e_5.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 1
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise E, Question 6
Question:
Solution:
t ( x ) = x2 6x + 5 { x , x 5{
Let y = x2 6x + 5 (complete the square)
y= (x3) 29+5
y= (x3) 24
This has a minimum point at ( 3 , 4 ) .
Note. Since x 5 is the domain, t(x) is a one-to-one function.
Change the subject of the formula to find t 1 ( x ) :
y= (x3) 24
y+4= (x3) 2
\y+4=x3
\y+4+3=x
t ( x ) = x2 6x + 5 { x , x 5{
has range t ( x ) , t ( x ) 0
So t 1 ( x ) = \ x + 4 + 3 and has domain x , x 0
Pearson Education Ltd 2008
file://C:\Users\Buba\kaz\ouba\c3_2_e_6.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 2
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise E, Question 7
Question:
2x + 1
The function h(x) is defined by h ( x ) = x2
x, x2 .
(b) Find h 1 ( 3 ) .
(d)Find the elements of the domain that get mapped to themselves by the
function.
Solution:
5
(a) As x 2 h ( x ) 0 and hence h ( x )
(b) To find h 1 ( 3 ) we can find what element of the domain gets mapped to 3.
So h ( a ) = 3
2a + 1
a2 =3
2a + 1 = 3a 6
7=a
So h 1 ( 3 ) = 7
2x + 1
(c) Let y = x 2 and find x as a function of y.
file://C:\Users\Buba\kaz\ouba\c3_2_e_7.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 2 of 2
y ( x 2 ) = 2x + 1
yx 2y = 2x + 1
yx 2x = 2y + 1
x ( y 2 ) = 2y + 1
2y + 1
x= y2
2x + 1
So h 1 (x) = x, x2
x2
Hence the inverse function has exactly the same equation as the function. But
the elements don't get mapped to themselves, see part (b).
file://C:\Users\Buba\kaz\ouba\c3_2_e_7.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 2
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise E, Question 8
Question:
(a) f
1 ( x ) clearly stating its domain
(a)Let y = 2x2 3
y + 3 = 2x2
y+3
2 = x2
y+3
\ 2 =x
file://C:\Users\Buba\kaz\ouba\c3_2_e_8.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 2 of 2
2a2 3 = a
2a2 a 3 = 0
( 2a 3 ) ( a + 1 ) = 0
3
a= 2 , 1
Therefore a = 1
Pearson Education Ltd 2008
file://C:\Users\Buba\kaz\ouba\c3_2_e_8.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 5
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise F, Question 1
Question:
(b)
file://C:\Users\Buba\kaz\ouba\c3_2_f_1.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 2 of 5
(c)
(d)
(e)
file://C:\Users\Buba\kaz\ouba\c3_2_f_1.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 3 of 5
(f)
Solution:
file://C:\Users\Buba\kaz\ouba\c3_2_f_1.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 4 of 5
file://C:\Users\Buba\kaz\ouba\c3_2_f_1.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 5 of 5
file://C:\Users\Buba\kaz\ouba\c3_2_f_1.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 2
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise F, Question 2
Question:
(c) Find g 1 ( x ) .
(a) f
( 7 ) = 4 ( 7 2 ) = 4 5 = 20
g ( 3 ) = 33 + 1 = 27 + 1 = 28
1 1
h( 2) =32= = 9
32
(b) f
( x ) = 4 ( x 2 ) = 4x 8
This is a straight line with gradient 4 and intercept 8.
The domain tells us that x 0.
file://C:\Users\Buba\kaz\ouba\c3_2_f_2.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 2 of 2
Hence g 1 ( x ) = 3\ x 1 {x{
(d) fg ( x ) = f ( x3 + 1 ) = 4 ( x3 + 1 2 ) = 4 ( x3 1 )
file://C:\Users\Buba\kaz\ouba\c3_2_f_2.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 2
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise F, Question 3
Question:
file://C:\Users\Buba\kaz\ouba\c3_2_f_3.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 2 of 2
file://C:\Users\Buba\kaz\ouba\c3_2_f_3.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 2
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise F, Question 4
Question:
(a) y
= 2x + 7 is a straight line of gradient 2 passing through 7 on the y axis.
The domain is given as x 0.
file://C:\Users\Buba\kaz\ouba\c3_2_f_4.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 2 of 2
x7
g1(x) = 2 and has domain x 7
(c)
file://C:\Users\Buba\kaz\ouba\c3_2_f_4.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 2
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise F, Question 5
Question:
Solution:
(a) f
: x 4x 1
Let y = 4x 1 and change the subject of the formula.
y + 1 = 4x
y+1
x= 4
x+1
Hence f 1 : x 4
3 3
(b) gf ( x ) = g ( 4x 1 ) = 2 ( 4x 1 ) 1 = 8x 3
3
Hence gf : x 8x 3
3
The domain would include all the real numbers apart from x = 8 (i.e. where
8x 3 = 0).
(c) If 2f ( x ) = g ( x )
3
2 ( 4x 1 ) = 2x 1
file://C:\Users\Buba\kaz\ouba\c3_2_f_5.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 2 of 2
3
8x 2 = 2x 1
( 8x 2 ) ( 2x 1 ) = 3
16x2 12x + 2 = 3
16x2 12x 1 = 0
b \ b2 4ac
Use x = 2a with a = 16, b = 12 and c = 1.
12 \ 144 + 64 12 \ 208
Then x = 32 = 32 = 0.826 , 0.076
Values of x are 0.076 and 0.826
Pearson Education Ltd 2008
file://C:\Users\Buba\kaz\ouba\c3_2_f_5.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 2
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise F, Question 6
Question:
Solution:
(a)
For x 1, f ( x ) = x
This is a straight line of gradient 1.
At point x = 1, its y coordinate is 1.
For x > 1, f ( x ) = x 2
This is a straight line of gradient + 1.
At point x = 1, its y coordinate is also 1.
The graph is said to be continuous.
1
(b) There are two values at which f ( x ) = 2 (see graph).
file://C:\Users\Buba\kaz\ouba\c3_2_f_6.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 2 of 2
Point a is where
1 1
x= 2 x= 2
Point b is where
1 1
x2= 2 x=1 2
1 1 1
The values of x for which f ( x ) = 2 are 2 and 1 2.
file://C:\Users\Buba\kaz\ouba\c3_2_f_6.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 2
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise F, Question 7
Question:
(a) Find f 1 ( x ) .
Solution:
file://C:\Users\Buba\kaz\ouba\c3_2_f_7.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 2 of 2
file://C:\Users\Buba\kaz\ouba\c3_2_f_7.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 2
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise F, Question 8
Question:
3
g:x x
x, x0
Solution:
file://C:\Users\Buba\kaz\ouba\c3_2_f_8.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 2 of 2
1.5 1.5 3
(c) gf ( 1.5 ) = g = g =g( 3) = = 1
1.5 2 0.5 3
(d) If g ( x ) = f ( x ) + 4
3 x
= +4 x x2
x x2
3 ( x 2 ) = x x + 4x ( x 2 )
3x 6 = x2 + 4x2 8x
0 = 5x2 11x + 6
0 = ( 5x 6 ) ( x 1 )
6
x= 5 , 1
6
The values of x for which g ( x ) = f ( x ) + 4 are 5 and 1.
file://C:\Users\Buba\kaz\ouba\c3_2_f_8.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 1 of 2
Solutionbank
Edexcel AS and A Level Modular Mathematics
Exercise F, Question 9
Question:
2
g:x x
x, x>0
1
(a) Show that f ( x ) = (x1) (x+1)
.
Solution:
x 1
(a) f (x) = x+1
x2 1
x 1
= (x+1) (x1) (x+1)
x x1
= (x+1) (x1) (x+1) (x1)
x (x1)
= (x+1) (x1)
1
= (x+1) (x1)
file://C:\Users\Buba\kaz\ouba\c3_2_f_9.html 3/9/2013
Heinemann Solutionbank: Core Maths 3 C3 Page 2 of 2
1 2
(c) gf (x) =g = =2
( x 1 ) ( x + 1 ) 1
(x1) (x+1)
(x1) (x+1)
1 =2 x1 x+1
If gf ( x ) = 70
2 ( x 1 ) ( x + 1 ) = 70
( x 1 ) ( x + 1 ) = 35
x2 1 = 35
x2 = 36
x= 6
Pearson Education Ltd 2008
file://C:\Users\Buba\kaz\ouba\c3_2_f_9.html 3/9/2013